"You're Fired, " Says the Robot: The Rise of Automation in the Workplace, Technophobes, and Fears of Unemployment. (April 2018) - McClure, Paul K.
The rapid adoption of new technologies in the workplace, especially robotics and artificial intelligence (AI), has motivated some researchers to determine what effects such technologies may have. Few scholars, however, have examined the possibility that a large segment of the population is apprehensive about the quick pace of technological change and encroachment into modern life. Drawing from economic projections about the future of the digital economy and from literature in the sociology of technology and emotions, this article explores whether certain fears of technology exacerbate fears of unemployment and financial insecurity. Using data from Wave 2 of the Chapman Survey of American Fears ( N = 1, 541), I find that there exists a sizable population of "technophobes" or those who fear robots, AI, and technology they do not understand. Technophobes are also more likely than nontechnophobes to report having anxiety-related mental health issues and to fear unemployment and financial insecurity. With advances in robotics and AI, the threat of technological unemployment is discussed as a real concern among a substantial portion of the American population.